Divided Fictions : Fanny Burney and Feminine Strategy - Straub, Kristina, 1951- (Book collections on Project MUSE., 1987)
Today Fanny Burney's venture into authorship would not be questionable. She was, after all, a daughter of a celebrated musician, and the Burney family was know to the circle of Samuel Johnson and Hester Thrale. Yet as Kristina Straub ably shows, the public recognition which followed the publication of her first novel placed Fanny Burney in a situation of disturbing ambiguity. Did she become famous or notorious? Was she a prodigy or a freak? In this study of Burney, Straub not only describes and analyzes the disturbing transition of a writer's self-awareness as a woman and a literary artist fro.